PERSUASIVE STRATEGIES USED BY AGUNG SEDAYU GROUP IN THE INFOMERCIAL, METRO TV - Iqbal Firmansyah; Esther H Kuntjara (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
This study is conducted to find out the types of persuasive strategies which were used in Agung Sedayu Group’s infomercial.  It is aimed to seek the types of persuasive strategies used by the hosts and the representative team of Agung Sedayu Group in the infomercial. The writer uses the theories of persuasive strategies by Beebe (2012). The types of persuasive strategies theories are enhancing your credibility, using logic and evidence, and using emotion to persuade. In addition, the writer uses theory of social factor by Holmes (2001) as the supporting theory. This research uses qualitative supported by quantitative methods to reveal which strategy that mostly used by the participants. In the analysis, the writer found out that the most dominant persuasive strategy used by the hosts is using emotion to persuade 161 (31.8%). Moreover, the most dominant persuasive strategy used by the representative team is enhancing your credibility 113 (22.3%).